2015
DOI: 10.1089/thy.2014.0235
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Hashimoto's Thyroiditis Negatively Affects the Evolution of Subclinical Hypothyroidism in Children Irrespective of Other Concomitant Risk Factors

Abstract: The association with HT exerts a negative influence on the evolution over time of mild SH, irrespective of other concomitant risk factors. In children with mild and HT-related SH, the risk of a deterioration in thyroid status over time is high (53.1%), while the probability of spontaneous TSH normalization is relatively low (21.9%). In contrast, in children with mild and idiopathic SH, the risk of a deterioration in thyroid status over time is very low (11.1%), whereas the probability of spontaneous TSH normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 21 publications
5
36
0
2
Order By: Relevance
“…Furthermore, the results of the present study confirm, on the basis of a more prolonged prospective evaluation, the recent inference that underlying HT negatively affects the natural course of SH in children, irrespective of other concomitant risk factors (12). In fact, when compared with group A girls, those belonging to group B exhibited both decreased probabilities of TSH normalization and an increased risk of thyroid function deterioration over time, irrespectively of whether HT-related SH was or was not Another peculiar aspect of the present study is that the patient series with HT-related SH was in turn divided in three subcohorts of girls with or without chromosomopathies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the results of the present study confirm, on the basis of a more prolonged prospective evaluation, the recent inference that underlying HT negatively affects the natural course of SH in children, irrespective of other concomitant risk factors (12). In fact, when compared with group A girls, those belonging to group B exhibited both decreased probabilities of TSH normalization and an increased risk of thyroid function deterioration over time, irrespectively of whether HT-related SH was or was not Another peculiar aspect of the present study is that the patient series with HT-related SH was in turn divided in three subcohorts of girls with or without chromosomopathies.…”
Section: Discussionsupporting
confidence: 90%
“…In the children with HT-related mild SH, it has been just recently reported that the evolution of thyroid function tests seems to be frequently characterized by a deterioration over time, whereas such risk is very low in the children with idiopathic SH (12). However, the available prospective studies on the natural history and prognosis of SH in children are very few and based on 2-3 years follow-up investigations (12,13,14,15,16), which hampers the ability of drawing firm conclusions about the relevance of those findings.…”
Section: Introductionmentioning
confidence: 99%
“…A worsening of thyroid function was indeed observed after 3 years of follow-up among 21.4% of children with HT compared with 13.6% of patients with isolated hyperthyrotropinemia in a retrospective multicenter study [57]. These data were further confirmed in a 2-year prospective study that documented an increased risk of progression to overt hypothyroidism among children with mild SH associated with HT (53.1%) with respect to children with a mild nonautoimmune form (11.1%) [59]. …”
Section: Mild Hypothyroidism In Childrenmentioning
confidence: 79%
“…16 On the other hand, it is well known that SH may have a different outcome in idiopathic cases [21][22][23][24][25] and in those with an underlying HT. [26][27][28][29] It has clearly been shown that in children without HT or other thyroid diseases, DS may be associated with higher TSH levels, probably due to an inherent TSH setting disorder which seems to be peculiar to DS. 30 On the basis of such findings, these authors concluded that diagnosis of SH might be overestimated in DS and that L-T4 therapy in these patients should be contemplated only when TSH values are HT diagnosis due to the initial finding of a transient hyperthyroid biochemical picture, but at that time they had been negative.…”
Section: Resultsmentioning
confidence: 99%